COVID-19: effective policymaking depends on trust in experts, politicians, and the public. Issue 1 (2nd January 2021) - Cairney, Paul; Wellstead, Adam
Abstract: In a crisis, almost-instant choices about who to trust or distrust could make a difference between life and death. Trust is necessary for cooperation, coordination, social order, and to reduce the need for coercive state imposition. During a pandemic, people need to trust experts to help them understand and respond to the problem, governments to coordinate policy instruments and make choices about levels of coercion, and citizens as they cooperate to minimize infection. We compare these general requirements with specific developments in the UK and US, identifying: the variable reliance by elected politicians on scientific experts, worrying levels of distrust in elected leaders, and a shift from a trust-based to more impositional forms of government action (with more variation in responses in the US). While trust is difficult to define and measure, these examples show that people miss it when it is gone.